(3GdMeGjI GdLfGFjI ddeYdheGJ GdeSLdI GdcJQhfjG (B/ s - (3YeQ CHh GdaJhM YHOGdYXje GdMeGei s; (3eCehf eMeO SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3CUHMJ GdMGLI edMI dJONd GdeTQY GdLfGFj GdeUQj HJLQje hYbGH GdCfeGW GdeNJdaI ddLQjeI GdeYdheGJjI , Jdc GdXGgQI GdELQGejI GdeSJMOKI , dPdc cGf VQhQjkG Cf fbSe gPg GdQSGdI Edi bSejf jSHbgeG aUd JegjOj CaQOfGg ddMOjK Yf GdMGSH GdBdj hechfGJg GdeGOjI hGdefWbjI , hYf GdeYdheGJjI cYde ef GdYdhe hcLQjeI ef GdLQGFe , CeG GdbSe GdChd abO NUUfGg GdOQGSI GdXGgQI GdELQGejI dLQGFe GdeYdheGJ GdeSLdI EdcJQhfjkG hbSefGg Edi HGHjf, GdChd JMOKfG ajg Yf GdSeGJ GdQFjSjI ddLQjeI GdeYdheGJjI MjK GdeLQe GdeYdheGJj hGdeLfj Ydjg aj GdLQjeI GdeYdheGJjI , hOhGaY GQJcGHgG , Ke JMOKfG Yf GdeYdheGJ hhSGFd GdGYJOGA YdjgG , hGdKGfj JMOKfG ajg Yf GdTQYjI GdLfGFjI ddLQjeI GdeYdheGJjI , hGdeYfi HjGf GdbhGYO GdbGfhfjI GdeJYdbI Ch GdNGUI HGdLQjeI GdeYdheGJjI aj eNJda GdfXe GdbGfhfjI (B... (3hGdbSe GdKGfj NUUfGg dOQGSI GdLhGfH GdbGfhfjI dLQGFe GdeYdheGJ GdeSLdI EdcJQhfjkG hbSefGg Edi HGHjf JMOKfG aj GdChd Yf LQGFe GdeYdheGJ GdeQJcHI aj EWGQ LQGFe GdCehGd cGdSQbI hGdfUH hNjGfI GdCeGfI , ebGQfjf aj Pdc Hjf GdLQjeI aj VhA GdbhGYO GdYGeI haj fWGb GdeYdheGJjI , CeG GdHGH GdKGfj abO JMOKfG ajg Yf LQGFe GdeYdheGJ GdeQJcHI aj EWGQ LQGFe GdZT GdeYdheGJj cLQGFe GdONhd ZjQ GdeTQhY ddfXe GdeYdheGJjI hJRhjQgG hEJdGagG , Ke NJefG MOjKfG HNGJeI ChVMfG ajgG fJGFL gPg GdOQGSI hJhUjGJgG(B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B566-583s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdLQjeI GdeYdheGJjIs; (3LQGFe GdZT GdeYdheGJi s; (3LQGFe GdceHjhJQs; (3GdeYdheGJ GdLfGFjI GdeSLdI s; (3GdJSLjd GdEdcJQhfj ddeYdheGJ s; (3GdMSGHGJ GdHfcjI s; (3GdCSQGQ GdegfjI s; (3GdJLSS s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs